The Role of Job Satisfaction as a Mediation of Perceived External Prestige and Deviant Behavior - Novalien Carolina Lewaherilla; Gerrit M Pentury; Victor Huwae; Rachma Atamimi (Enrichment : Journal of Management, 2022)
This study aims to explain the influence of external perceptions of prestige on deviant behavior and the role of job satisfaction as a mediating variable for employees of PT. Ambon Branch Telecommunications. The type of research used in this study is explanatory with a quantitative approach. The population in this study were employees of PT. Telkom Indonesia Ambon Branch. The sample of this research was taken as many as 42 respondents. Hypothesis testing using SEM-PLS analysis with the help of SmartPLS 3 software. The results showed that external perception of prestige had a significant effect on deviant behavior, external perception of prestige had a significant effect on job satisfaction. Job satisfaction has a significant effect on deviant behavior,